Langerhans cell histiocytosis in children – a disease with many faces. Recent advances in pathogenesis, diagnostic examinations and treatment - Jezierska, Michalina; Stefanowicz, Joanna; Romanowicz, Grzegorz; Kosiak, Wojciech; Lange, Magdalena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2018)
Langerhans cell histiocytosis is a rare clonal disease characterized by the proliferation of CD1a-positive immature dendritic cells. The purpose of this article was to present an updated review of recent advances in the pathogenesis, clinical features, imaging and treatment of this disease. The discovery of oncogenic BRAF mutations and the presence of proinflammatory cytokines and chemokines confirmed the unusual characteristics of this disease. Currently, children with organ involvement who do not have a good response to chemotherapy and have neurodegeneration or diabetes insipidus are the most problematic patients. Further research is needed to improve the results of treatment.